The influence of mode of anaesthesia for caesarean delivery on neonatal Apgar scores in the Czech Republic and Slovakia: secondary analysis of the results of an international survey in 2015 - Harazim, Hana; Stourac, Petr; Blaha, Jan; Grochova, Monika; Klozova, Radka; Noskova, Pavlina; Seidlova, Dagmar; Richterova, Stanislava; Svoboda, Michal; Jarkovsky, Jiri; Silova, Xenia; Jezova, Bozena; et al. (Biomedical papers, 2019)
Aims: The purpose of this international survey was to describe the impact of current practices and techniques of caesarean section on the neonatal Apgar score in the Czech Republic (CZE) and Slovakia (SVK). Methods: All Czech and Slovak departments that provide obstetric anaesthesia were invited to participate in a one-month (November 2015) prospective study that monitored in details all peripartum anaesthetic practices, delivered by anaesthesiologists. Participating centers recorded all data on-line in the CLADE-IS database (Masaryk University, CZE). Results and Discussions. We collected data of 10119 women who delivered 10226 newborns. A caesarean section was recorded in 25.1% of deliveries (CZE 23.2%; SVK 30%). General anaesthesia was used for caesarean section in 37.5% of the cases (CZE 40%, SVK 33%). There was no statistically significant difference in the Apgar score lower than 7 in the 1, 5 or 10 min in groups of general and regional anaesthesia for caesarean section, when only elective sections of in-term babies with birth weight over 2500 g were analyzed. We found no statistically significant differences in the Apgar score in newborns of women intubated for caesarean section in rocuronium (n=21; 2.2%) and suxamethonium (n=889; 93%). Conclusion: We found no difference in neonatal outcomes in groups of general and regional anaesthesia for caesarean section when only out-of-risk newborns were analyzed. The risk factors were identified as follows: an acute caesarean section, preterm babies, birth weight less than 2 500 g, born in perinatological center and multiple pregnancy - second baby. Trial Registration: ClinicalTrials.gov (ID: NCT02380586) https://clinicaltrials.gov/ct2/show/NCT02380586
Keywords: caesarean section; Apgar score; rocuronium; suxamethonium; international survey; general anaesthesia; rapid sequence induction; neonatal outcome